Chile's Structural Fiscal Surplus Rule : A Model-Based Evaluation - Kumhof, Michael (IMF Working Papers; Working Paper ;, 2009)
The paper analyzes Chile's structural balance fiscal rule in the face of copper price shocks originating in foreign copper demand. It uses a version of the IMF's Global Integrated Monetary and Fiscal Model (GIMF) that includes a copper sector. Two results are obtained. First, Chile's current fiscal rule performs well if the policymaker puts a small weight on output volatility (relative to inflation volatility) in his/her objective function. A more aggressive countercyclical fiscal rule can attain lower output volatility, but there is a trade-off with (somewhat) higher inflation volatility and (much) higher volatility of fiscal variables. Second, given its current stock of government assets, Chile's adoption of a 0.5% surplus target starting in 2008 is desirable from a business cycle perspective. This is because the earlier 1% target would have required significant further asset accumulation that could only have been accomplished at the expense of greater volatility in fiscal instruments and therefore in GDP.